Analysis of Aqua's Crisis Communication in the “Drilled Wells” Issue: Framing, Expectation Gap, and Reputation Recovery Strategy from an Scct Perspective - Siti Retno Wulandari; Ana Noviani; Anggie Nur Fitrianti; Christania Pingkan Putrinita; Meyta Roida Rebecka Hutapea (Pelopor Publikasi Akademika, 2026)
PT Tirta Investama’s (AQUA) response when receiving a visit from West Java Governor Dedi Mulyadi became a public conversation after the agenda was recorded and uploaded on social media. The company’s answer when asked about the water source that had been used triggered a communication crisis, especially after the mention of “drilled wells.” This issue triggered a perception-based reputation crisis due to the expectation gap between the image of the AQUA brand as an AMDK sourced from “natural mountain water” and the public’s understanding of the technical terms of water resource management. This study uses a qualitative approach with a case study method, utilizing secondary data in the form of online media reports, official company statements, and social media content. The analysis was carried out within the framework of Navigating the Case Analysis Process and supported by Situational Crisis Communication Theory (SCCT). The results of the analysis show that the crisis experienced by AQUA falls into the category of accidental cluster, with a moderate level of attribution of responsibility. Although AQUA responded to the crisis relatively quickly and transparently, technical and defensive communication strategies have not been fully effective in closing the gap in public perception. This research emphasizes the importance of empathetic, educational, and dialogical crisis communication in the digital age, as well as the consistency of cross-channel framing to restore trust and organizational reputation.